Comparing Different Algorithms to Estimate two Parameters of Weighted Rayleigh Distribution - Rwaa Saleh Mohamed AL-Safar (Iraqi Journal for Administrative Sciences, 2024)
This paper deals with transforming a one parameter Rayleigh distribution, to another family called weighted two parameters Rayleigh, where the weighted functions are necessary when sampling done through samples of different size, also we work of estimating its two parameters using methods of maximum likelihood and moment estimators, and percentile estimators, the comparison has been done through simulation, we need to generate the values using a program of incomplete Gamma function. Keywords: two parameters weighted Rayleigh distribution, maximum likelihood estimators and moment estimators, percentile estimators.